Missy Piggle-Wiggle and the sticky-fingers cure - Martin, Ann M., 1955-; Parnell, Annie (Martin, Ann M., 1955- Missy Piggle-Wiggle book ;, 2018)
Even though she, her upside-down house, and its animal occupants are under quarantine with the Winter Effluvia, Missy Piggle-Wiggle manages to dispense cures to the misbehaving children of Little Spring Valley.